Statutory and common law interpretation - Greenawalt, Kent, 1936- (New York ; Oxford : Oxford University Press, 2013)
Kent Greenwalt's second volume on aspects of legal interpretation analyzes statutory and common law interpretation suggesting that multiple factors are important for each, and that the relation between them influences both.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Keywords: Law -- Interpretation and construction; Common law; Law -- Methodology